Resolving Urban Land Disputes: Lessons from the Portland, Oregon Region - Sullivan, Edward J. (AESOP, 2015)
The Portland Metro area is the largest urban area in Oregon. The Metro planning agency makes binding planning decisions for the region, including establishing an urban growth boundary (UGB) to provide sufficient urban lands for 20 years. After successful challenges to additions to urban lands, the Oregon legislature established new rules for “urban reserves” for 20-50 years. Urban reserves are presumptively the next additions to the UGB. To maximize discretion, the legislature authorized Metro to balance certain unweighted “factors” (instead of fixed criteria) in designating urban reserves. The paper recounts the controversy that revolved around the attempt by Washington County to add substantial farmland to urban reserves to accommodate employment growth. Resource land preservation is a high value in Oregon’s planning system. Opponents suggested that adding a large amount of resource lands could not be justified by the findings purportedly “balancing” these factors. The urban reserves process failed when the Oregon Court of Appeals held that the use of the factors did not obviate justification of addition of resource lands to urban reserves. The legislature intervened, setting the urban growth boundary and most reserve areas by statute. The paper provides an assessment of this regional urban reserve process – factors in lieu of criteria, temptation to solve UGB problems at the legislature, the need for more predictable “safe harbors” for future urban designations, and accountability through uniform and transparent growth projections. While deference may be given regional planning decisions, those decisions must be coherent and justified by an adequate factual basis.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015